2022
DOI: 10.3390/app122312099
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cartilage Conduction Hearing Aid, Bone Anchored Hearing Aid, and ADHEAR: Case Series of 6 Patients with Conductive and Mixed Hearing Loss

Abstract: Cartilage conduction hearing aids (CC-HA), bone anchored hearing aids (Baha), and ADHEAR are good choices to improve hearing in patients who cannot use air conduction hearing aids because of aural atresia or continuous otorrhea. As there are many overlaps in the characteristics of these devices, we conducted a comparative trial of CC-HA, Baha, and ADHEAR. We provided patients with the opportunity to select their devices. The data of 6 patients who underwent comparative trials in our department between October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The patients in the present study achieved benefits comparable to those reported in previous studies [17]. CC hearing devices have better aided hearing levels than ADHEAR [19], which may result from the difference not only in the transducer output, but also place of fixation, thickness of the fixation tape, and mass of the transducer. Regarding the fixation place, the thresholds for cartilage stimulation are better than those for mastoid stimulation at low frequencies when the simple-type transducer is used [28].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The patients in the present study achieved benefits comparable to those reported in previous studies [17]. CC hearing devices have better aided hearing levels than ADHEAR [19], which may result from the difference not only in the transducer output, but also place of fixation, thickness of the fixation tape, and mass of the transducer. Regarding the fixation place, the thresholds for cartilage stimulation are better than those for mastoid stimulation at low frequencies when the simple-type transducer is used [28].…”
Section: Discussionsupporting
confidence: 82%
“…However, it can provide sufficient audiological benefits for daily use [16][17][18]. The aided thresholds of CC hearing devices are better than those of ADHEAR [19]. The performances of CC hearing devices in speech recognition are comparable to those of BC devices, such as BAHA, although the aided thresholds were slightly higher [20].…”
Section: Introductionmentioning
confidence: 97%
“…A summary of the characteristics in the 12 included studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] is shown in Table 2 . There was a total of 447 patients with various peripheral auditory disorders (excluding those from study [ 24 ] due to overlapping participant groups with study [ 20 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Speech outcomes were equivalent, except for the 15dB SNR condition. Regarding the differences between BC devices and CC hearing aids, Nishiyama et al compared the benefits of the BAHA, CC hearing aids, and ADHEAR (MED-EL, Innsbruck, Austria) [ 31 ]. They reported data from six patients who underwent comparative trials.…”
Section: Clinical Studies In Countries Other Than Japanmentioning
confidence: 99%
“…Kitama et al measured the sound localization in patients with unilateral atretic ears using a CC hearing aid, BAHA, and ADHEAR on the atretic ear. Compared with the un-aided condition, no significant improvement was observed in any of the three aided conditions [ 31 ]. However, the comparison was provided for only one patient.…”
Section: Sound Localization In Bilateral Atretic Earsmentioning
confidence: 99%